Predictive value of ApoB/ApoA-I for recurrence within 1 year after first incident stroke - Lin, Jie; Si, Zhihua; Wang, Aihua (Frontiers in Neurology, 2024)
Background ApoB/ApoA-I ratio is a reliable indicator of cholesterol balance, particularly in the prediction of ischemic events risk. The aim of this study was to investigate the prognostic value of ApoB/ApoA-I for stroke recurrence within 1 year after the first incident. Methods We retrospectively included patients who were first diagnosed with acute (<7 days after onset) ischemic stroke. Blood samples were collected on admission, and serum ApoB and ApoA-I concentrations were measured. We analyzed the relationship between ApoB/ApoA-I ratio and ischemic stroke recurrence within 1 year. Results A total of 722 patients with acute ischemic stroke were included, of whom 102 experienced stroke recurrence within 1 year, with a recurrence rate of 14.1%. Serum ApoB/ApoA-I concentrations on admission were higher in patients with stroke recurrence at 1 year compared with those with a good prognosis (P < 0.001). The Kaplan-Meier survival curve revealed a significant difference in cumulative stroke recurrence rates across ApoB/ApoA-I tertiles (log-rank P-value < 0.001). A positive correlation between the ApoB/ApoA-I ratio and the risk of stroke recurrence within 1 year was demonstrated using Cox regression analysis, which remained significant after adjusting for traditional risk factors [hazard ratio (HR) 4.007, 95% confidence interval (CI) 1.661–9.666]. This relationship was particularly strong in patients with LAA stroke (HR 4.955, 95% CI 1.591–15.434). Subgroup analysis further revealed that a high ApoB/ApoA-I ratio was strongly associated with stroke recurrence regardless of whether patients had high or low LDL-C levels. Discussion ApoB/ApoA-I ratio, measured during the acute phase of the first stroke, was positively correlated with the risk of stroke recurrence within 1 year.